Implementation of Online-Based Administrative Services in Electronic Population Application Services (LAKSE) in Batam City - Safitri, Mena; Dompak, Timbul (Dinasti International Journal of Management Science, 2025)
This study aims to analyze and describe the implementation of the Electronic Population Application Service (LAKSE) at the Population and Civil Registration Office of Batam City. The research employs a descriptive qualitative method, focusing on documentation studies to systematically explain the features, benefits, and challenges of the LAKSE application. The LAKSE application represents a digital innovation designed to streamline population administration processes, offering online services for obtaining essential documents such as identity cards, family cards, and birth or death certificates. Findings indicate that the LAKSE application has successfully improved service delivery by reducing queues, enhancing accessibility, and facilitating efficient data management. The application simplifies administrative procedures through its user-friendly interface and online submission system, allowing users to process requests from their homes. However, challenges persist in raising public awareness and ensuring widespread adoption, particularly among individuals less familiar with digital tools. In conclusion, the LAKSE application serves as an effective innovation for modernizing population administration services in Batam City. To maximize its potential, increased dissemination of information and technical support are crucial to fostering broader community participation. This research underscores the importance of digital transformation in public services to enhance efficiency, accessibility, and citizen satisfaction.